PENINGKATAN KETERAMPILAN MEMBACA DAN BERPIKIR KRITIS SISWA SMA MELALUI METODE STRATTA - Lia Nur Safitri; Ardila Putri Cantika; Evi Chamalah (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to improve the reading and critical thinking skills of high school students through the Stratta method. Stratta method is derived from the writing of Leslei Stratta in his book Pattems of Language so it is called the Stratta method. In this method of teaching literature there are three stages that must be done, namely the exploration phase, the interpretation phase and the recreation stage. The research method used in this research is research and development (research and development / R & D). Data collection in this study was conducted by examining the current state of teaching and learning of high school students today. This study produced several scenarios to improve the reading and critical thinking skills of high school students through the Stratta method. Improved reading skills and critical thinking in students can be developed and produce a work both literary or non-literary. In each learning there are several scenarios that can be applied during the teaching and learning process. The exploration stage in the study of literature there are 5 scenarios and in non-literary learning there are 6 scenarios. At the interpretation and recreation stages there are 4 scenarios in literary and non-literary learning.